Effects of Educative–Supportive Using Line Application Program on Ability and Anxiety Among Care Givers of Advanced Cancer Patients - Sanganate, Anong; Kimsungnoen, Nipa; Namjantra, Rachanee (NU Journal of Nursing and Health Sciences, 2024)
The purpose of this quasi-experimental one group pre-posttest design aimed to study the effects of the Educative Supportive using Line Application program on ability and anxiety among care givers of advanced cancer patients. Thirty-five caregivers of patients with advanced cancer who was purposively selected, The program was developed based on Orem’s educative-supportive nursing system as a conceptual framework.(2001) The Educative Supportive using Line Application program on ability and anxiety among caregivers of advanced cancer patients in 4 weeks. The research instrument comprised: 1) experiment instrument which was the Educative Supportive using Line Application program on ability and anxiety among caregivers of advanced cancer patients. 2) data collection instrument including a demographic data and caregivers’ ability and anxiety questionnaire of advanced cancer patients. Caregivers’ ability and anxiety questionnaire of advanced cancer patients were collected before and after the program and analyzed by descriptive statistics, wlicoxon signed rank test. After 4 weeks.It was found that caregivers’ ability in caring for patients with advanced cancer increased significantly. (Z= -5.171, p=.000) and caregivers’ anxiety of patients with advanced cancer decrease significantly. (Z= -5.17, p=.000). The results of this study can be used as a guideline for improving the ability of caregivers and reducing their anxiety.